1976
DOI: 10.1002/pssa.2210380108
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of deep centres of chlorine-doped zinc sulfide crystals

Abstract: Deep centres of the ZnS: C1 single crystals are investigated by the method of impurity electroabsorption (IEA) and photoconductivity (PhC). I n accordance with estimations fulfilled a number of the levels obtained are ascribed to Vin; (VznCls)' and Vin and also t o (VznGazn)', whose energy levels are obtained in a previous paper. In the induced IEA spectrum two fixed peaks are found whose satellite displacements A are described by different dependences on the modulating voltage U, namely A -U1/3 and -U W . Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1977
1977
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The 2.8 eV peak, which appears in the IEA spectrum of "pure" ZnS only, and which was observed earlier [7], we have attributed to Vin as in [7].…”
Section: Spectral Distribution Of Zeamentioning
confidence: 66%
See 1 more Smart Citation
“…The 2.8 eV peak, which appears in the IEA spectrum of "pure" ZnS only, and which was observed earlier [7], we have attributed to Vin as in [7].…”
Section: Spectral Distribution Of Zeamentioning
confidence: 66%
“…I n [6] in which ZnS : Ga single crystals were investigated, the 3.18 eV peak was ascribed by us to the (VznGaZn)' complex, in which VP, and gallium are separated by the nearestneighbour distance. Analogous complexes were considered also in [7]. If one assumes that doping with indium is similar to doping with Ga and C1 and leads with great probability to the formation of complexes consisting of Vin and an impurity atom at the nearest-neighbour distance, i.e.…”
Section: Spectral Distribution Of Zeamentioning
confidence: 99%
“…To date, the nature of the luminescence centers, causing the blue and green bands of Cu in ZnS, is well studied [8][9][10][11][12][13]. In the works [11][12][13][14][15], it is shown that the center of the green glow of copper with λ max ~ 505…535 nm is isolated copper ion, replacing zinc ion in the ZnS lattice. The blue band with λ max ~ 450…465 nm is related to formation of associates like to the close DA-pair Cu i -Cu Zn [16].…”
Section: Resultsmentioning
confidence: 99%
“…Possibly, the presence of a fluxing agent leads to increasing the partial pressure of Cl [17], which increases the solubility of copper in the basis of luminophore and results in additional association of copper ions and formation of centers like to the close DA-pair Cu i -Cu Zn and, accordingly, to combusting of PL blue band. Effect of Cl, as a co-activator, on the spectral composition and PL intensity is related with necessity to compensate charge of internal defects in material, which is in sufficiently details described in the works [8][9][10][11][12][13][14]. In [14], it has shown that even a small amount of the Cl impurity in ZnS conduces introduction of copper into the sites of Zn sublattice, or filling the Zn vacancies, which leads to an increase in contribution of the green band to luminescence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation